North Slope Borough shoreline change risk WebGIS usability workshop. - Michael Brady (Arctic Data Center, 2017)
In April 2016, local and regional North Slope manager perspectives were collected on usability of a beta version shoreline change risk WebGIS developed for the Arctic Slope covering the National Petroleum Reserve - Alaska (NPR-A) and the Arctic National Wildlife Refuge (ANWR). The WebGIS is a collaborative effort with the North Slope Borough (NSB). Transcripts from the audio recorded workshop were stored in a MS Excel file. The purpose of the data set is to assess usability of the WebGIS as a formative evaluation effort to develop a shoreline change risk WebGIS for Alaska's Arctic Slope using a collaborative mapping and Instructional Systems Design (ISD) process.